Antioxidant Activity of Different Parts of Isgin (Rheum ribes L.) - OKTAY, MUNIR; YILDIRIM, ALI; BILALOGLU, VAHIT; GULCIN, ILHAMI (Asian Journal of Chemistry, 2010)
Total antioxidant activity of ether, ethanol and water extracts of different parts of isgin (Rheum ribes) was investigated using thiocyanate method for antioxidant activity. Significant differences (p < 0.05) were found between the control and the samples containing of isgin (Rheum ribes) extracts. Butylated hydroxyanisole (BHA), a powerful synthetic antioxidant was used as a positive control. All of the extracts were compared with BHA, but were not statistically significant difference (p > 0.05). Among the extracts, ethanol extract of peel has the highest antioxidant activity. In addition, reducing power, total phenolic content, radical scavenging activity and superoxide anion radical scavenging activity of isgin (Rheum ribes) extracts were examined, in this study. The phenolic content analyses of extracts were expressed as gallic acid equivalents per 1000 μg extract.